OSL Dating of Paleo-Shorelines at Dagze Co, Central Tibetan Plateau - Wu, Yang; Chen, Yiwei; Huang, Long; Ding, Ping; Cui, Hao; Wei, Gangjian (Frontiers in Earth Science, 2022)
Well-preserved paleo-shoreline systems suggest lake shrinkage occurred in a vast region of the Tibetan Plateau, indicating dramatic paleo-environmental changes that linked closely to variations in Asian monsoon precipitation, glacial meltwater and evaporation. The elevation and chronology of these shoreline features can be used to reconstruct lake level fluctuation history and regional paleo-climate. Here, we report Optically Stimulated Luminescence (OSL) dating of 14 sediment samples from three of seven paleo-shorelines at south of Dagze Co, central Tibetan Plateau, using coarse grain quartz and K-feldspar. Two fine grain silt samples were also measured. The results suggest that (1) The highest paleo-shoreline for Dagze Co has an elevation around 4525 m (+55 m above modern lake), with an age estimated to be 9.1±0.5 ka to 9.6±0.6 ka, suggesting a relative humid condition in the early Holocene. (2) After that the lake level dropped ~20 m and was relatively stable (+35 m) from about 8-5 ka, implying a dry condition with reduced runoff. Lake level further declined for ~40 m since about 5 ka. (3) The general trend of shrinkage for Dagze Co broadly matches many studies from adjacent lakes, suggesting a common pattern of lake's evolution on the plateau in the late Quaternary. The long-term decreasing trend of Asian monsoon precipitation should be the main reason.